Von der „ville en crise” zur Metropolitan European Growth Area: aktuelle Transformationsprozesse der Metropolregion Marseille — Aix-en-Provence - Megerle, Heidi (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
The seaport Marseille fought for decades with the image of a “ville en crise” after losing the colonial overseas markets. The planning of a free-trade-area in the Mediterranean region as well as the changeing of paradigms in the French regional planning system led to significant dynamics. This correlated with one of the most ambitious urban renewal projects (Euroméditerranée) in Europe. The great cities of the Mediterranean region play an important role for the achievement of the Lisbon strategy. In close co-operation with adjoining communities the metropolitan region Marseille-Aix-en-Provence strives for a key position in the northern part of the Mediterranean.